Impact of inflation and exchange rate towards Foreign Direct Investment (FDI) in construction sector in Malaysia: an empirical study on the cross-sectional data by using EViews, 1992 2012 / Intan Maizura Abdul Rashid ... [et al.] - Abdul Rashid, Intan Maizura; Abu Samah, Irza Hanie; Hassan Basri, Haslina; Yeong, Shao Jieh (Universiti Teknologi MARA, Perlis, 2017)
The purpose of the studies is to investigate the impact of inflation and exchange rate towards Foreign Direct Investment (FDI) in Construction Sector in Malaysia. The construction reacts as important sectors in generating large income for people and revenue for the country. Therefore, FDI in construction sector can improve the quality of growth, and aid to achieving the goal of country development. In this study, the FDI in Construction Sector react as dependent variable and the independent variable are exchange rate and inflation rate in Malaysia. The primary contribution of this study can help both domestic and foreign firms to learn more about Malaysian economy and the FDI of Malaysia, particularly in construction sector. As this sector grows rapidly day-by-day, it is essential for investor and firms to understand more about the economic aspects, as well as the finance aspects. As these determinants may be proved to be significant towards FDI, the investor and firms can get such information and gain competitive advantage in the construction sector in Malaysia. The empirical analysis of this study was performed by using econometric methods that is Ordinary Least Square (OLS) regression which involved Augmented Dickey-Fuller (ADF) unit root test, and diagnostic tests, Heteroscedasticity Test model and Breush-Godfrey Serial Correlation LM Test. Lastly, the findings of this research paper have an important policy implications and show that all these issue may still need further devotion in future research.